A AUDITOR EXPERIENCE, LOCUS OF CONTROL AND OBEDIENCE PRESSURE ON AUDITOR JUDGMENT AT PUBLIC ACCOUNTING OFFICE, JAKARTA SELATAN - Hendrawan, Agus (FEB - Universitas Lampung, 2023)
Purpose:This study aims to examine the effect of Audit Experience, Locus of Control and Obedience Pressure on Audit Judgment as well as simultaneously. Audit Experience, Locus of Control and Obedience Pressure as independent variables. Audit Judgment as dependent variable. Methodology/Approaches: The research method used is quantitative by using primary data questionnaires to the Public Accounting Firm in Central Jakarta area. The sampling process is carried out using the Simple Random Sampling method and this study uses a slovin formula with the result of 73 respondents. The data obtained is processed by data analysis techniques using SPSS version 25. Results/Finding:The results indicated that: (1) audit experience has no effect and is not significant on audit judgment; (2) locus of control has a positive and significant effect on audit judgment; (3) obedience pressure has a positive and significant effect on audit judgment; (4) audit experience, locus of control and obedience pressure have a significant effect on audit judgment simultaneously. Limitations:The scope of this research is only conducted in Central Jakarta, this study only examines three factors that influence the making of audit judgment so that it is possible that other factors that can influence audit judgment may not be known. Keywords:Audit Experience; Locus of Control; Obedience Pressure; Audit Judgment.